Preference of university students to get involved in the agribusiness sector - Md Isa, Mohd Azwardi; Mutum, Adam Dilip (2004)
The last two decades, Malaysia has focused on industry for its economic development. Currently, the trends of economic development have moved towards agriculture, thus, agribusiness sector will become more important in the future. There are several government agencies directly involved in the development of agricultural sector such as Federal Agriculture Marketing Agency (FAMA) and the Malaysia Agriculture Development Authority (MADA). This exploratory study seeks to identify the preference and tendency of the Universiti Utara Malaysia (UUM) students. A questionnaire composed of closed ended questions was used to draw out responses from 318 students from three faculties in UUM. This study found that majority of the students agreed having a business idea is important. They also agreed that choice and type of business is very significant. However, most of them refuse to undertake agribusiness as their future career. The findings indicate that UUM students generally have high entrepreneurship spirit and likely to involve in business activity. Surprisingly, the students were not keen to involve in agribusiness sector. The study suggest that government agencies involved should play more proactive roles in disseminating the information such as incentives, training and funding for agribusiness sector to the university students.